Chemical composition and biological activity of essential oil of Kaempferia galanga: a review. Issue 5 (3rd September 2018) - Munda, Sunita; Saikia, Pompy; Lal, Mohan
Abstract: Kaempferia galanga is one of the most industrially important medicinal plants belongs to Zingiberaceae family and contains high-valued essential oil of medicinal and industrial importance. The essential oil of K. galanga has got huge market potential in India and world. The present market value of essential oil varies from US600 to 700 per kilogram on the international market. The major chemical constituents of the essential oil of K. galanga are ethyl-p-methoxy-cinnamate, ethyl cinnamate, 1, 8-cineole, borneol, camphene, linoleoyl, methyl-cinnamate and pentadecane. These chemical components show various anti-microbial activities and nutraceutical properties. Due to its wealth of pharmacological applicability, K. galanga is a high-valued medicinal plant of industrial importance. In this review, we present, up to date information regarding the chemical composition and biological activity of essential oil of K. galanga which offer a new perspective on the research on biochemical and molecular characterization of elite chemical components for pharmacological applications and commercial utility.